Optimal Control of Vaccination and Treatment of Varicella Disease (Chicken Pox) - Aisyah, Ranti Rivani; Firdaus, Hamidah 'Alina; Napitupulu, Herlina; Anggriani, Nursanti (Jurnal Matematika Integratif, 2024)
Varicella, or chickenpox, is an infectious disease that can affect anyone, especially children under the age of 10. Vaccination and medication are key measures in reducing the number of infections and the risk of Varicella infection. A mathematical SEITR model has been developed to describe this disease mathematically. Stability of the equilibrium points and the basic reproduction number of the developed model were then determined. Control was also applied to vaccination and medication with the aim of minimizing the infected population and the costs of vaccination and treatment. These control measures were incorporated into the SEITR model. Finally, Pontryagin’s Maximum Principle was used in the optimization process. This optimal control process significantly reduced the number of infected individuals, thereby effectively controlling the spread of Varicella.